2006
DOI: 10.1159/000098813
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Two Less-Calcemic Vitamin D Analogs (Paricalcitol and QW-1624F<sub>2</sub>-2) in Squamous Cell Carcinoma Cells

Abstract: The active metabolite of vitamin D3 (1α,25-dihydroxyvitamin D3, calcitriol) has potent antitumor activities in vitro and in vivo in multiple cancers. Concerns about induction of hypercalcemia by calcitriol and the desire for more potent agents have prompted development of less-calcemic vitamin D analogs. These studies demonstrate that two vitamin D analogs, 19-nor-1α,25-dihydroxyvitamin D2 (paricalcitol) and 1α-hydroxymethyl-16-ene-24,24-difluoro-25-hydroxy-26,27-bis-homovitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Concerns about the induction of hypercalcemia by calcitriol and the desire for more potent agents have prompted development of less calcemic vitamin D analogues. EB1089 has been shown to regulate the differentiation and proliferation of multiple human cancer cell lines and thus is a potential therapeutic agent for cancers (23,24). In the present study, we have shown for the first time that EB1089 significantly suppresses the growth of human laryngeal SCCs in vitro; this might reflect the general antitumor activity of EB1089.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Concerns about the induction of hypercalcemia by calcitriol and the desire for more potent agents have prompted development of less calcemic vitamin D analogues. EB1089 has been shown to regulate the differentiation and proliferation of multiple human cancer cell lines and thus is a potential therapeutic agent for cancers (23,24). In the present study, we have shown for the first time that EB1089 significantly suppresses the growth of human laryngeal SCCs in vitro; this might reflect the general antitumor activity of EB1089.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that the vitamin D analogue, 1-hydroxymethyl-16-ene-24,24-difluoro-25-hydroxy-26,27-bis-homovitamin D 3 , can modulate cell cycle regulators, including increasing mRNA and protein levels of p21 and CDK2 and increasing p27 protein expression in SCCs (24). p57 is a potent inhibitor of several G 1 cyclin/CDK complexes and its overexpression leads to cell cycle arrest in G 1 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to circumvent this adverse reaction have included the use of high intermittent doses of 1,25D 3 that can be administered to patients with prostate and other cancers without apparent toxicity [4]. Further, a number of vitamin D analogues with lower calcemic effects have been synthesized, which retain the differentiation and antiproliferative activities of the parent compound in myeloid leukemia cells and other cancer cell lines [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The use of vitamin D analogues for potential treatment of cancers212223 and autoimmune diseases2425 has been gaining momentum in preclinical research in addition to its classical treatment for osteoporosis. As supraphysiological doses of vitamin D cause hypercalcemia, potential analogues with reduced calcemic effects and improved efficacy are being actively developed.…”
Section: Discussionmentioning
confidence: 99%